2003
DOI: 10.1103/physreve.67.011504
|View full text |Cite
|
Sign up to set email alerts
|

Rotational magnetic particles microrheology: The Maxwellian case

Abstract: An experimental method based on the rotational dynamics of a magnetic probe is reported to measure the local viscoelasticity of soft materials on microscopic scales. The technique is based on the alignment of dipolar chains of submicrometer magnetic particles in the direction of an applied magnetic field. On one hand, light scattering is used to detect the chains' oscillations over a 0.001-100 Hz frequency range when submitted to an oscillating magnetic field and leads to global microrheological measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 20 publications
0
92
0
Order By: Relevance
“…The first factor is the shape factor κ for a linear chain of spherical particles including the effect of hydrodynamic interactions. Specifically, Wilhelm et al [29] empirically derived a shape factor valid for any size of the chain:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first factor is the shape factor κ for a linear chain of spherical particles including the effect of hydrodynamic interactions. Specifically, Wilhelm et al [29] empirically derived a shape factor valid for any size of the chain:…”
Section: Discussionmentioning
confidence: 99%
“…The opposing viscous drag torque consists of 4 factors [11,27,29]. The first factor is the shape factor κ for a linear chain of spherical particles including the effect of hydrodynamic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are both powerful and quantitative. Several studies, however, reported the use of anisotropic objects such as disks [13], rods [14][15][16][17][18][19][20] and wires [21][22][23], for both passive [13,21,23] and active [14, 16-18, 22, 24-28] µ-rheology. Some recent work has shown that rod or wire based µ-rheology experiments could also bring significant advances to the field [18-20, 23, 27].…”
Section: -Introductionmentioning
confidence: 99%
“…40 The method used here resembles an experimental technique where the mobility of a probe molecule is studied using a controlled external magnetic field. 41 The time evolution of the N-particle system under periodic boundary conditions is described bẏ…”
Section: B Non-equilibrium Molecular Dynamicsmentioning
confidence: 99%